2017
DOI: 10.1007/s00125-017-4342-z
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of action of metformin

Abstract: Metformin is a widely-used drug that results in clear benefits in relation to glucose metabolism and diabetes-related complications. The mechanisms underlying these benefits are complex and still not fully understood. Physiologically, metformin has been shown to reduce hepatic glucose production, yet not all of its effects can be explained by this mechanism and there is increasing evidence of a key role for the gut. At the molecular level the findings vary depending on the doses of metformin used and duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
1,363
2
50

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,684 publications
(1,431 citation statements)
references
References 62 publications
16
1,363
2
50
Order By: Relevance
“…Reduction in hepatic glucose output is the principal action of metformin although its mechanism(s) have not been clearly identified. The previously held view that metformin reduces glucose synthesis via activation of AMPK has been challenged; recent data indicate that lowered hepatic glucose output with metformin may result from inhibition of electron transport in mitochondrial respiratory Complex I [29] (this is described in more detail in the commentary by Rena et al in this issue of Diabetologia [30]), as well as antagonism of glucagon action in the liver [31].…”
Section: Mechanisms Of Metformin Action In Target Tissues Relevant Tomentioning
confidence: 99%
“…Reduction in hepatic glucose output is the principal action of metformin although its mechanism(s) have not been clearly identified. The previously held view that metformin reduces glucose synthesis via activation of AMPK has been challenged; recent data indicate that lowered hepatic glucose output with metformin may result from inhibition of electron transport in mitochondrial respiratory Complex I [29] (this is described in more detail in the commentary by Rena et al in this issue of Diabetologia [30]), as well as antagonism of glucagon action in the liver [31].…”
Section: Mechanisms Of Metformin Action In Target Tissues Relevant Tomentioning
confidence: 99%
“…Metformin and AICAR both activate AMPK. Previous work, including experiments in which AMPK activity was genetically ablated, indicate that AMPK is not essential for regulation of HGP, although both drugs activate AMPK 13, 14, 15, 17, 18. In the current study, we used AMPK activation purely as a marker of drug entry into the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using cAMP analogues have shown previously that the T2D drug metformin and 5‐Aminoimidazole‐4‐carboxamide ribonucleoside (AICAR) repress cAMP‐stimulated hepatocyte glucose production (HGP) 13, 14, 15. Inside cells, AICAR is phosphorylated by adenosine kinase to form ZMP, which then mimics AMP to activate AMPK 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…incorporation into the diabetes pharmacopeia. Interestingly, and despite this popularity, there still remains controversy about the drug's precise mechanism of action, although most data point to a reduction in hepatic glucose production being predominately involved (described further by Rena et al in this issue of Diabetologia) [4]; although, recent data suggests that some of the drug's effect may involve the stimulation of intestinal release of incretin hormones. Herein, we will review the most salient aspects of the clinical use of metformin in individuals with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%